Information shocks, jumps, and price discovery: Evidence from the US Treasury market - George J. Jiang; Ingrid Lo; Adrien Verdelhan (Bank of Canada, 2008)
We examine large price changes, known as jumps, in the U.S. Treasury market. Using recently developed statistical tools, we identify price jumps in the 2-, 3-, 5-, 10-year notes and 30-year bond during the period of 2005-2006. Our results show that jumps mostly occur during prescheduled macroeconomic announcements or events. Nevertheless, market surprise based on preannouncement surveys is an imperfect predictor of bond price jumps. We find that a macroeconomic news announcement is often preceeded by an increase in market volatility and a withdrawal of liquidity, and that liquidity shocks play an important role for price jumps in U.S. Treasury market. More importantly, we present evidence that jumps serve as a dramatic form of price discovery in the sense that they help to quickly incorporate market information into bond prices.
Keywords: G12; G14; 330; Financial markets; Wertpapierhandel; Schatzpapier; Wirtschaftslage; Ankündigungseffekt; Informationsverbreitung; Börsenkurs; Volatilität; Schock; USA